Causes and Remedies of Slope Failures & Landslides in Malaysia - Chin, Khee Yong (2015)
This project report is intended primarily to serve as a subject for the undergraduate civil engineering student to complete their Diploma in Civil Engineering Program. The purpose of this project was to enables the student to do design, research, the factor and making personal decision about a given project title that is given by supervisor. For the successful of this project, student will have applied a range of techniques for generating, evaluating and selecting design concepts to meet specified requirement. It also help student for understanding the nature of design concept and needed a range of interpersonal skill. The common factor and remedies of landslide and slope failure that I research was an interesting topic that will happen in Malaysia. After my research the common factor that cause of the landslide arc, Water, Earthquake, Wildfire and Volcanoes. These factor are the cause of the landslide and earthquake. In this situation I going to design a cantilever wall. The cantilever wall that j design dimension of 4.Sm in height, located behind the mosque in Dataran Nilai, which consistency of backfill with density 6= 1400 and angle of repose a— 10°. When I go thru the design part. I realized factor has to be consider before get it into design of cantilever wall; soil condition types of backfill, surcharge loads, foundation stability and other factor. I also applied a formula that j has learned in the text books when doing my design part.